PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Mulia Alim; Uniq Destriana (Universitas Muhammadiyah Tangerang, 2016)
This study was to determine whether the audit committee of institutional ownership and firm size (size) positive effect on the performance of companies, both partially and simultaneously. Agency theory is the theory behind a conflict of interest between managers and owners (shareholders). The manager as agent and owner of the company as a principal. Agents often misuse company resources with an excessive amount. Agency conflict is a situation where managers often make decisions that benefit themselves rather than the interests of shareholders. While the minimal information that principals have difficulty to find out if the agent had acted in accordance with the wishes of the principal or even hurt the company.